2019
DOI: 10.1002/suco.201800347
|View full text |Cite
|
Sign up to set email alerts
|

Prestressing concrete members with fibre‐reinforced polymer reinforcement: State of research

Abstract: The technology of prestressing concrete structures has been a well‐established field in structural engineering since the last century. Nowadays, new materials developed for reinforcing concrete structures, such as fibre‐reinforced polymers (FRPs), open further possibilities for engineers. FRP tendons are more and more often investigated as an efficient and suitable material for prestressing, and there are already some field applications of this technology. This paper aims to describe the current state of knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 58 publications
(100 reference statements)
0
46
0
1
Order By: Relevance
“…When FRP cables are used either for prestressing structural elements or supporting bridge decks, their anchorages need to be properly designed to reduce the cable stress state. Different types of anchorage systems have been proposed in technical and scientific literature so far, and a state of the art review is reported in different works [10][11][12][13][14][15]. These systems include bonded and mechanical devices.…”
Section: Introductionmentioning
confidence: 99%
“…When FRP cables are used either for prestressing structural elements or supporting bridge decks, their anchorages need to be properly designed to reduce the cable stress state. Different types of anchorage systems have been proposed in technical and scientific literature so far, and a state of the art review is reported in different works [10][11][12][13][14][15]. These systems include bonded and mechanical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Um Schäden infolge von Querpressungen zu vermeiden, ist die Zugkraft möglichst gleichmäßig in die Verankerung einzuleiten. Mit Verankerungen bei Stäben und Litzen aus kohlenstofffaserverstärktem Kunststoff (CFK) wurden bereits gute Ergebnisse erzielt [1, 2]. Für Textilbewehrung sind die aufgeführten Verankerungen jedoch nicht praktikabel [3, 4] und andere Vorspannungssysteme befinden sich noch in der Entwicklungsphase [5].…”
Section: Einführung Und Motivationunclassified
“…Hoyer effect, referred to as “wedge action,” was investigated in 1939 . It is active exclusively in transfer zone in pretensioned concrete members . When a prestressing strand is pretensioned, the tensile force causes a reduction of the strand diameter by Poisson's ratio as the strand is elongated.…”
Section: Three Bond Mechanismsmentioning
confidence: 99%